Load Flow Computations in Different Coordinate Systems for a Power System with UPFC - Okon, Tomasz; Wilkosz, Kazimierz (Elektronika ir Elektrotechnika, 2016)
This paper deals with the Newton-Raphson load flow solution for a power system with embedded UPFC, when this device is modeled with the use of so-called Voltage Source Model. The aim of the paper is to present results of the original investigation of the mentioned load flow solution from the numerical point of view. The carried out investigation give the base for the statement that performing the load flow computations in the rectangular coordinate system is much more beneficial than in the polar coordinate system, which is most often used in the existing papers. DOI: http://dx.doi.org/10.5755/j01.eie.22.5.16338